Applying the ontological approach to design the factor-goal analysis information system; Control and Communications (SIBCON) - Silich M. P. Mariya Petrovna; Gribkov E. I. Egor Igorevich; Osipova V. V. Viktoriya Viktorovna; Silich V. A. Viktor Alekseevich (2015, 2015)
Title screen